Endoscopic ligation of the patulous eustachian tube as treatment for autophony1. (15th October 2012) - Rotenberg, Brian W.; Busato, Gian‐Marco; Agrawal, Sumit K.
Abstract Objectives/Hypothesis: Patulous eustachian tube remains a challenging management problem in otolaryngology. The autophony experienced by this patient population can be severe, and as yet no reliable surgical method exists to reduce or eliminate this annoying symptom. Our objective was to develop a novel endoscopic technique to assist these patients. Study Design: Longitudinal case series. Methods: A prospective longitudinal study was conducted of a series of consecutive patients undergoing surgery for patulous eustachian tube. Under transnasal endoscopic guidance, using a combination of fat plugging, endoluminal cauterization, and suture ligation, 14 ears underwent surgical treatment during a 4‐year period. The main outcome measure assessed was the level of autophony present after surgery as compared to baseline. Audiometric outcomes, surgical time, and complications were also recorded. Results: There was sustained satisfactory subjective improvement in the autophony in 12 of the 14 ears (85.7%) at primary surgery, with nine of these 12 ears (75%) demonstrating full autophony cessation. Wilcoxon signed rank test showed a significant improvement in autophony in the study population compared to baseline (z = 3.16, P < .001). The mean operating length of time per ear over the full duration of our series was approximately 45 minutes. Postoperative audiometry showed that surgery had no impact on hearing. Conclusions: Multilayer endoscopic ligation of the patulous eustachian tube resulted in a high autophony improvement rate. The procedure is technically straightforward, and results were sustained at 6‐month follow‐up. Laryngoscope, 2013